The effect of a home-based orofacial exercise program on oral aperture of patients with systemic sclerosis: A single-blind prospective randomized controlled trial - Nihan CÜZDAN; İpek TÜRK and Volkan ÇİFTÇİ and Didem ARSLAN and Muharrem Cem DOĞAN and İlker ÜNAL (Archives of Rheumatology, 2021)
Objectives: This study aims to evaluate the effect of a home-based orofacial exercise program on the oral aperture (OA) of systemic sclerosis (SSc) patients. Patients and methods: This single-blind prospective randomized controlled study performed between March 2017 and January 2019 included 56 SSc patients (3 males, 53 females; mean age 52.9±10.6 years; range, 31 to 70 years) with an OA of <40 mm. Patients were divided into two groups. Group 1 (n=28, mean age 53.8±9.6 years) was given orofacial exercise program twice a day for one month in addition to oral hygiene care advices, followed by no activity for the next month. Group 2 (n=28, mean age 50.0±11 years) received oral hygiene care advices for the first month followed by the same exercise program for the next month. Patients’ OA was measured at baseline, and at first and second months. Results: After the first month, OA increased in Group 1 (p<0.001), whereas no change was observed in Group 2 (p=0.579). At the end of two months, there was no additional increase in Group 1 (p=0.352), while there was a significant increase in Group 2 (p<0.001). There was no difference between OAs of the groups at the end of the trial (p=0.564). Conclusion: Our results suggest that home-based orofacial exercise program improves OA of SSc patients.